GLORIFYING AND DECONSTRUCTING OBAMA`S SPEECH IN INDONESIA (English Education Journal, 2011)
A text has an almost infinite number of possible interpretations. And theinterpretation themselves, declares some deconstructionists, are just as creativeand important as the text being interpreted. This study is an attempt to explainhow the interpretations on Obama's speech make meanings in the way they do.Apart from the realization of experiential, interpersonal and textual meanings aswell as the field, tenor and mode and their context of culture, it is revealed thatText 1 under this investigation illustrates the ideological claim that the personalappeal of an orator, appeals to the emotions of the audiences through theappropriate choice of themes and metaphors of the oration, and appeals to logicor reason should be possessed by a shrewd orator and politician, who is alwaysable to put his audiences into his frame of mind everywhere he delivers hisspeeches. Whereas Text 2 illustrates the ideological claim that despite apersonal power of persuasion you possess, one is tempted to ask how an officialvisit means anything. While it is true that you spent a considerable years in acity during your childhood, your statement should not be overly emphasized,analyzed nor treated as anything but political rhetoric aimed at further boostingthe vivacious intellectual crowd. As readers of texts, we need to develop skillsto be able to make explicit the ideological positions encoded.